Ritual and religious experience in early christianities the spirit in between - McCollough, David John 1971-; University of Durham (Tübingen Mohr Siebeck, 2022)
In diesem Band stellt David John McCollough die weit verbreiteten Annahmen in Frage, dass Paulus dachte, der Geist werde durch die Wassertaufe vermittelt, dass „Rechtfertigung“ nicht auf Erlebnissen beruhe und nichts mit Ritualen zu tun habe, dass Lukas inkohärent oder ein schlechter Redakteur gewesen sei und dass die Wassertaufe der wichtigste Initiationsritus der frühen Christenheit gewesen sei.Inhaltsübersicht1. Introduction 2. Exegetical Methodology2.1 Introduction2.2 Acts: The Dual Problems of Historicity and Intelligibility2.3 Methodological Problems2.4 Methodological Solutions2.5 Acts and History Again: Which Historical Audience? 3. Exegesis3.1 Pauline Epistles3.2 Luke-Acts 4. Interpretation4.1 Introduction4.2 Understanding Notions of Culture and Their Relationship to Spirit Possession4.3 What’s So Special About Initiation? Ritual Form Theory and Lukan Baptism(s)4.4 Spirit Impartation as Performative Ritual4.5 Commitment Signalling Theory: Costly and Charismatic4.6 Identity Fusion in the Early Christian Sect: How Initiatory Spirit-Possession Formed Social Bonds Among the Early Christians4.7 Sacred Values and the Early Christian Sect4.8 Emotion and the Early Christian Sect4.9 Mediation in the Early Christian Sect4.10 Why Did People Become Christians in the First Century? 5. Conclusion
In this volume, David John McCollough offers a narratological, discourse analysis, and literary exegesis of texts in Paul and Luke-Acts, followed by interpretation with social anthropological approaches. The author challenges common assumptions about Paul, such as that Paul thought the spirit to be communicated through water baptism, or the notion that ‘justification’ was non-experiential and unrelated to ritual. He refutes the view that Luke was either incoherent or unconcerned or a poor editor of sources regarding early Christian initiation practices and questions the belief that water baptism was the cardinal initiation rite among early Christianities. He instead argues that spirit possession marked by dissociation and glossolalia was the cardinal initiation ritual for Pauline and Lukan communities.Survey of contents1. Introduction 2. Exegetical Methodology2.1 Introduction2.2 Acts: The Dual Problems of Historicity and Intelligibility2.3 Methodological Problems2.4 Methodological Solutions2.5 Acts and History Again: Which Historical Audience? 3. Exegesis3.1 Pauline Epistles3.2 Luke-Acts 4. Interpretation4.1 Introduction4.2 Understanding Notions of Culture and Their Relationship to Spirit Possession4.3 What’s So Special About Initiation? Ritual Form Theory and Lukan Baptism(s)4.4 Spirit Impartation as Performative Ritual4.5 Commitment Signalling Theory: Costly and Charismatic4.6 Identity Fusion in the Early Christian Sect: How Initiatory Spirit-Possession Formed Social Bonds Among the Early Christians4.7 Sacred Values and the Early Christian Sect4.8 Emotion and the Early Christian Sect4.9 Mediation in the Early Christian Sect4.10 Why Did People Become Christians in the First Century? 5. Conclusion
Archivierung/Langzeitarchivierung gewährleistet
Keywords: A counter-imperial gospel in 1 and 2 Thessalonians?; Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Justification; Christian Initiation; Early Christianity; Anthropology; Narratology; Neues Testament; Array; Jesus tradition in 1 Thessalonians; Enargeia; Hochschulschrift